Acute effects of static and dynamic stretching exercises on isokinetic strength of hip flexion-extension in male handball players - Alp, Mahmut (Progress in Nutrition, 2020)
This study aimed to examine and compare the acute effects of static stretching (SS) and dynamic stretching (DS) on the hip flexor and extensor concentric (CON) isokinetic peak torque (PT) at 60°/s and 180°/s angular speeds in well-trained male handball players. A total of 14 male handball players (mean age 20.28±1.06 years; handball experience 11.50±1.45 years; height 180.64±6.34 cm; weight 73.35±6.60 kg; body mass index 22.49±1.90 kg/m2) who train at least 4 days a week, 120 min a day, were recruited in this study. Players were tested for hip flexor and extensor isokinetic PT at 60°/s and 180°/s angular speeds before and 4 min after three different stretching exercise sessions, namely, non-stretching (NS), SS, and DS, with 48-h rest intervals in a randomized crossover study design. Statistical analysis revealed that no significant difference (p>0.05) was observed among the stretching exercises in hip CON isokinetic PT values at 60°/s and 180°/s. The findings of our study are that SS exercises do not have a tension deficit in PT; DS exercises showed that PT did not increase the hip flexor and extensor CON isokinetic muscle movement more than SS exercises in male handball players. Based on previous studies, the findings suggest that athletes who are accustomed to static or dynamic stretching movements in male handball players may be less susceptible to stretch-induced power loss.